2019
DOI: 10.1021/acs.chemmater.9b03399
|View full text |Cite
|
Sign up to set email alerts
|

Oxide Ion Conduction and Surface Exchange Reactions of Mixed Conductive La0.65Ca0.35FeO3−δ Based on Oxygen Permeation Study

Abstract: La0.65Ca0.35FeO3−δ (LCF6535) displayed higher oxygen permeation flux (J O2 ) compared to La0.6Sr0.4Co0.2Fe0.8O3−δ (LSCF) and could potentially replace the typical cathodes employed in solid oxide fuel cells. However, the oxide ion conduction and surface exchange reaction of the LCF6535 have not been studied thus far. This study investigates the ion conductivity and surface exchange reaction of LCF6535 by simultaneous investigation of the oxygen permeation flux and oxygen chemical potential. The ion conductivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Using a similar experimental setup, our research group previously described the OCP for the LCaF membrane. 17 The EMF measured by the YSZ sensor on the oxidized and reduced surfaces are denoted by E s(rich) and E s(lean) , respectively. These two EMFs were generated due to dioxygen activity on the corresponding sides of sample surfaces and can be explained following the Nernst equation below 17,18…”
Section: Experimental Partmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a similar experimental setup, our research group previously described the OCP for the LCaF membrane. 17 The EMF measured by the YSZ sensor on the oxidized and reduced surfaces are denoted by E s(rich) and E s(lean) , respectively. These two EMFs were generated due to dioxygen activity on the corresponding sides of sample surfaces and can be explained following the Nernst equation below 17,18…”
Section: Experimental Partmentioning
confidence: 99%
“…Where The bulk EMF (E bulk ) corresponds to the oxygen activity through the volume of a sample can be estimated by the equation 17,18…”
Section: Experimental Partmentioning
confidence: 99%
“…15,16 To understand the surface exchange mechanism, a previous study examined influences of oxygen partial gradient on the surface oxygen chemical potential drop and J Od 2 in LCF. 17 reaction is restricted by surface density of electron−holes. Thus, it is highly necessary to examine the microscopic view by directly observing the chemical state at the surface during oxygen evolution and incorporation, hence the need for an operando experiment.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Applications of mixed conductive oxides are also commonly required to overcome the issue of slow surface exchange reactions at moderate temperature (<800 °C). , To understand the surface exchange mechanism, a previous study examined influences of oxygen partial gradient on the surface oxygen chemical potential drop and J O 2 in LCF . This study found that the concentration of electrons and holes on the surface of an LCF film affects the evolution of O 2 molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Oxides including mixed and high valence states of transition-metal cations are an important class of materials in energy-related technology fields. They are used, for example, as cathodes in solid oxide fuel cells and as ceramic membranes separating oxygen from air. The perovskite structure oxides like La 1 –x A x CoO 3−δ and La 1– x A x FeO 3−δ , where A is Ca, Sr, or Ba, are typical such compounds and are intensively studied. Controlling the valence state of the constituent transition-metal cations is a key for tuning the compound’s properties. We here focus on La 1– x Ca x FeO 3−δ -related compounds and investigate the mixed and high valence states of Fe.…”
Section: Introductionmentioning
confidence: 99%